2015
DOI: 10.1007/s10021-015-9851-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Metabolic Rates of Two Tropical Lakes in the Atlantic Forest of Brazil

Abstract: We studied the importance of environmental drivers for the seasonal dynamics of gross primary production (GPP), ecosystem respiration (R), and net ecosystem production in surface waters of two tropical lakes in southeast Brazil (Carioca-CA; and Dom Helvé cio-DH), 2011 and 2012, using high frequency measurements of dissolved oxygen. Metabolic rates were approximately twice as high during the fully mixed winter periods, compared to the summer periods. For both lakes, GPP was approximately 30% lower during the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…As the presence of chromophoric carbon in the water protects the aquatic organisms from harmful ultraviolet Optical properties in tropical systems radiation and from the excessive incidence of solar radiation (Zhang et al, 2007a), our results suggest that the photoinhibition of phytoplankton primary production observed in DH during summer by Brighenti et al (2015) is directly linked with the seasonal pattern of photobleaching of CDOM and nutrients availability, where both dependent of the sources and quality of DOM. Thereby, we demonstrated that the main source of DOM in DH come from the terrestrial input during the rainy period, reinforcing the importance of preserving the original forest surrounding the lakes to the global carbon cycle.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…As the presence of chromophoric carbon in the water protects the aquatic organisms from harmful ultraviolet Optical properties in tropical systems radiation and from the excessive incidence of solar radiation (Zhang et al, 2007a), our results suggest that the photoinhibition of phytoplankton primary production observed in DH during summer by Brighenti et al (2015) is directly linked with the seasonal pattern of photobleaching of CDOM and nutrients availability, where both dependent of the sources and quality of DOM. Thereby, we demonstrated that the main source of DOM in DH come from the terrestrial input during the rainy period, reinforcing the importance of preserving the original forest surrounding the lakes to the global carbon cycle.…”
Section: Discussionmentioning
confidence: 70%
“…Positive correlations between S 350-400 and nutrients (TP and TN) only during the rainy season suggest that microbial degradation in the epilimnion might be limited by nutrients during thermal stratification. Nutrient limitation of primary production during the rainy season in DH Lake was observed by Brighenti et al (2015) in a two year study of lake metabolism. In agreement with this Chla concentrations were lower in the rainy period in DH.…”
Section: Seasonality Of Optical Properties Between the Contrasting Symentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a greater input during rainy season, the water column stability in DH is large in this period (Brighenti et al 2015) and the allochthonous matter coming with runoff from rains remains retained below the thermocline due to differences in water temperature (Reynolds 2009). Redistribution of particulate matter into the upper mixed layers accordingly occurs during the dryer and colder season which therefore is characterized by less transparent water.…”
mentioning
confidence: 99%